SUNFLOWER STALKS AND LIGNOSULFONATE – ALTERNATIVE RAW MATERIALS FOR THE PRODUCTION OF ECO-FRIENDLY MEDIUM DENSITY FIBREBOARDS - Mihajlova, Julia; Savov, Viktor (Innovation in Woodworking Industry and Engineering design, 2023)
The main advantages of the technology for producing Medium Density Fibreboards (MDF) are the reduced requirements for wood raw material, the possibility of fabricating that type of product from sawmill residues and the potential of including other non-wood lignocellulosic raw materials in the composition of the panels. Such lignocellulose raw materials are residues from agriculture. In our country and worldwide, there are many successful studies for at least partial replacement of wood raw material with agricultural residues. Sunflower plantations are the second largest in our country, which is why they would be a significant source of non-wood lignocellulosic raw material. Another significant problem in MDF production is the presence of formaldehyde emissions from the panels. One of the main directions for solving this problem is replacing the traditional binders with alternative ones without formaldehyde emissions. These alternative binders should not significantly increase the cost of board production, maintain their performance, and, most importantly, not be hazardous to human health. This binder includes the so-called bio-based binders, of which lignin-based products are the most promising. A typical representative of such an alternative bio-based binder is lignosulfonate (methylated lignin). That leads to the relevance of a study on the possibility of partially replacing wood raw material with sunflower stalks and reducing the number of synthetic binders used in MDF by adding lignosulfonate in the adhesive system. As a result of the research on the influence of urea-formaldehyde resin content, lignosulfonate content, and pulp from sunflower stalks on the properties of thin MDF, the main conclusions were deduced, and recommendations were made on the practical use of these alternative raw materials.